Heat-inactivated Bifidobacterium bifidum MIMBb75 (SYN-HI-001) in the treatment of irritable bowel syndrome: a multicentre, randomised, double-blind, placebo-controlled clinical trial. (July 2020) - Andresen, Viola; Gschossmann, Jürgen; Layer, Peter
Summary: Background: Bifidobacterium bifidum MIMBb75 is one of a few probiotic strains that have been shown to be effective in the treatment of irritable bowel syndrome (IBS) and its symptoms. Non-viable strains might have advantages over viable bacteria for product stability and standardisation, as well as for tolerability because safety concerns have been raised for specific patient groups who are susceptible to infection. We aimed to assess the efficacy of non-viable, heat-inactivated (HI) B bifidum MIMBb75 (SYN-HI-001) in the treatment of IBS and its symptoms. Methods: We did a double-blind, placebo-controlled trial in which patients with IBS were recruited from 20 study sites in Germany and randomly assigned to receive either two placebo capsules or two capsules with a combined total of 1 × 10 9 non-viable B bifidum HI-MIMBb75 cells to be taken orally once a day for 8 weeks. Eligible patients were diagnosed with IBS according to Rome III criteria and had abdominal pain (≥4 on an 11-point numerical rating scale) on at least 2 days during a 2-week run-in phase. Patients with chronic inflammatory bowel diseases, systemic diseases, cancer, autoimmune diseases, with an intake of antipsychotic medications 3 months before study start, or with an intake of systemic corticosteroids within 1 month before study start were excluded. Randomisation was in a 1:1 ratio according to a computer-generated blocked list. Patients, investigators, clinical monitors, project managers, and statisticians were masked to the randomisation. The primary composite endpoint was the combination of at least 30% improvement of abdominal pain and adequate relief of overall IBS symptoms being fulfilled in at least 4 of 8 weeks during treatment. Analysis of the primary endpoint included all randomly assigned patients receiving at least one dose of study medication and who had no severe protocol violation. Safety analysis included all patients who had taken at least one dose of the study medication and was based on frequency and severity of adverse events, laboratory evaluation, and global assessment of tolerability. This trial is registered with the ISRCTN registry, ISRCTN14066467, and is completed: the results shown here represent the final analysis. Findings: Patients were screened between April 15, 2016, and Feb 3, 2017, and 443 patients were allocated to the placebo group (n=222) or the B bifidum HI-MIMBb75 group (n=221). The composite primary endpoint was reached by 74 (34%) of 221 patients in the B bifidum HI-MIMBb75 group compared with 43 (19%) of 222 in the placebo group (risk ratio 1·7, 95% CI 1·3–2·4; p=0·0007). No serious adverse events occurred in the B bifidum HI-MIMBb75 group; seven adverse events suspected to be related to the study product were reported in the B bifidum HI-MIMBb75 group as were eight in the placebo group. No deaths were reported in this study. The most common reported adverse event with a suspected relationship to the study product was abdominal pain, which was reported in two (<1%) patients in the B bifidum HI-MIMBb75 group and one (<1%) in the placebo group. Tolerability was rated as very good or good by 200 (91%) patients in the B bifidum HI-MIMBb75 group compared with 191 (86%) in the placebo group. Interpretation: This study shows that B bifidum HI-MIMBb75 substantially alleviates IBS and its symptoms in a real-life setting. These results indicate that specific beneficial bacterial effects are mediated independently of cell viability. Funding: Synformulas.